Mutagenically separated PCR assay for rapid detection of M41L and K70R zidovudine resistance mutations in CRF01_AE (subtype E) human immunodeficiency virus type 1. - Myint, L; Ariyoshi, K; Yan, H; Frater, A; Auwanit, W; Pathipvanith, P; Yamada, K; Matsuda, M; Chiba, T; Fujita, K; McClure, M; Weber, J; et al. (2002)
A rapid zidovudine (ZDV) resistance genotypic assay was developed based on the mutagenically separated PCR (MS-PCR) technique to detect two ZDV-resistant mutations, M41L and K70R in CRF01_AE (subtype E). Endpoint dilution analysis revealed that the newly constructed MS-PCR assay could successfully detect three to nine copies of human immunodeficiency virus type 1 template RNA. The test against wild-type and mutant template mixtures in different ratios demonstrated that the assay could detect 10% minor population, at least. Fifty-one subtype E clinical samples were analyzed by the newly constructed MS-PCR assay and direct nucleotide sequencing. The concordance of the two assays was 92 and 100% in codons 41 and 70, respectively. The MS-PCR assay is a rapid, simple, and inexpensive assay that is highly sensitive in detecting mutant targets, including minor populations. Thus, it could be used as a powerful tool for epidemiological surveillance of drug-resistant mutations in developing countries.